Moving towards principles-based accounting standards: The impact of the new revenue standard on the quality of accrual accounting - HE, HUIYU, (Institutional Knowledge at Singapore Management University, 2023)
The new revenue standard (ASU 2014-09, codified in ASC 606 and ASC 340-40) establishes a comprehensive framework on accounting for contracts with customers and replaces most existing revenue recognition rules. The new guidance removes the inconsistencies and weaknesses of legacy guidance, while is more principles-based and requires more managerial judgements. Using as-reported data from structured filings to construct aggregate accruals that are potentially affected by the new revenue standard (i.e., sales-related accruals), I find that the new revenue standard increases the quality of sales-related accruals, as measured by future cash flow predictability. The increased cash flow predictability comes not only from the guidance on contract revenue (ASC 606) but also from the guidance on contract costs (ASC 340-40). The effects concentrate among firms conducting long-term sales contracts, especially over longer forecast horizons. Further analysis shows that the new revenue standard also increases the combined information content of financial statements and the capital market efficiency. However, the discretion under the new standard opens avenue for earnings management when firms face strong manipulation incentives.